2013
DOI: 10.4103/0028-3886.125275
|View full text |Cite
|
Sign up to set email alerts
|

Chin fasciculations in Madras motor neuron disease: A new clinical feature

Abstract: The characteristic features of Madras motor neuron disease (MMND) are onset in the young in the first two decades, sporadic occurrence, facial and bulbar paralysis, sensorineural hearing impairment, asymmetrical weakness of limbs and pyramidal signs with a slow progression. The majority of the cases reported are from South India. MMND variant has the additional features of optic atrophy and cerebellar signs. We are reporting a 48 year old female of MMND who had persistent fasciculations of chin, with electromy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Associated with this are pyramidal signs and sensorineural deafness. In some cases, optic atrophy, cerebellar involvement and chin fasciculations were also present 54 55. There have been single case reports from other countries including China, Thailand and Turkey.…”
Section: Atypical Asian Phenotypesmentioning
confidence: 99%
“…Associated with this are pyramidal signs and sensorineural deafness. In some cases, optic atrophy, cerebellar involvement and chin fasciculations were also present 54 55. There have been single case reports from other countries including China, Thailand and Turkey.…”
Section: Atypical Asian Phenotypesmentioning
confidence: 99%
“…This difference could be since all ring-enhancing lesions were thought to be tuberculomas previously because tuberculosis was considered the commonest disease in India. [16] [26,27,28] When an analysis was made between the neurological findings and EEG, both abnormalities of the neurological examination and epileptiform discharges were found in 24% of patients in the present study. Schumacher et al have demonstrated similar features in 52% of patients.…”
Section: Discussionmentioning
confidence: 48%